Konservierungswissenschaft schreibt Geschichte - Krack, Elisabeth (2012)
An overview of the academic courses of study and vocational trainings offered in the conservation and restoration of objects of decorative arts and metal in German-speaking countries points to a lack of continuity and identity. This is due to the fact that this field is a relatively young one and many universities have only offered degree courses since the 1990s. In Austria there are two Universities, the "Akademie der bildenden Künste" and the "Universität für angewandte Kunst". Both are located in Vienna and have a old-established academic experience. The long tradition particular to the field of restoration of objects of decorative arts at the University of Applied Arts Vienna is exceptionally. Early conservation and preservation research and restoration work started in the late 19th century. This is a distinctive feature, as other institutions with a similarly long history put their focus on the restoration of paintings and painting technique research instead. The "Kunstgewerbemuseum", todays Museum of Applied Arts Vienna, was founded 1863. In 1868 the school called "Kunstgewerbeschule" was attached. It is famous for its leading design-position during art nouveau an developed into todays University of Applied Arts Vienna. Both stood in close contact with the "K.K. Centralcommission". This historic preservation agency, established in 1850, concentrated in the preservation of monuments and historic buildings of the large Habsburg Empire. During the 19th century new emerging ideas of conservation where well known at "Kunstgewerbeschule" and "Kunstgewerbemuseum".Teaching staff at the school made in their annual reports notes of early restoration. But they did it as an additional business and therefore more detailed information is not given. Women in the studios for enamelwork (Adele von Stark) and the studio for textile work (Rosalia Rothansl) were about 1900 pioneers in field of object conservation. The first official class for conservation existed 1902 - 1910, named "Atelier für Kunstweberei und Restaurierung". A lot of information about the astonishing mordern ethics and methods in Conservation at that time can be extracted from two conferences that took place in Vienna: The First Arthistorical Congress in 1873 and the Enquete about Conservation of Art in 1904. Curators of the Museum of applied Arts and to a certain extent teaching staff of the "Kunstgewerbeschule" were involved with organisation and speeches.A new era for the conservation at University of Applied Arts Vienna started after World War Two. Otto Nedbal, a conservator experienced in metal crafts, was appointed at the university. He at first assumed the existing class for enamelwork. In 1964 he founded a new master class for restoration of metals and objects of enamel. But the content of teaching and the requirements for diploma thesis changed significant during the following forty years and this class evolved into today's Institute for Conservation and Restoration. The specialization of painting conservation was established by Nedbals successor Hubert Dietrich in 1980. In the course of a reorganization of the university in 2000 and the appointment of Gabriela Krist as head of the new conservation department, the new specializations of conservation of stone and textile were arranged. Eine Auswertung des aktuellen Studien- und Ausbildungsangebots der Konservierung und Restaurierung von kunsthandwerklichen Objekten und Metall im deutschsprachigen Raum zeigt, dass es an Kontinuität und Selbstverständnis mangelt. Grund dafür ist, dass es sich bei der Konservierungswissenschaft und Restaurierung um eine vergleichsweise junge akademische Disziplin handelt und zahlreiche Hochschulen erst in den 1990er Jahren begannen, entsprechende Curricula für diesen Fachbereich zu erstellen. Österreich verfügt über zwei Hochschulen, die Akademie der bildenden Künste und die Universität für angewandte Kunst, welche ein Konservierungs- und Restaurierungsstudium anbieten. Beide besitzen eine ungewöhnlich lange Tradition in der Ausbildung akademischer Restauratoren. An der Vorläuferinstitution der Universität für angewandte Kunst, der Wiener Kunstgewerbeschule, lässt sich die konservatorische und denkmalpflegerische Tätigkeit an Objekten des Kunstgewerbes bereits Ende des 19. Jahrhunderts festmachen. Bei Institutionen mit ähnlich langer Geschichte standen dagegen die Gemälderestaurierung und Maltechnikforschung im Fokus. Das Wiener Kunstgewerbemuseum, das heutige Museum für angewandte Kunst, wurde 1863 gegründet. 1868 erfolgte die Angliederung der für ihre führende Position im Design des Jungendstils berühmte Kunstgewerbeschule. Beide Einrichtungen kooperierten mit der "K.K. Centralcommission", der 1850 gegründeten Vorläuferinstitution des heutigen Bundesdenkmalamtes. Einige Professoren der Kunstgewerbeschule vermerkten in ihren Jahresberichten Restaurierungen, die aber nur neben der kreativen Tätigkeit ausgeführt worden waren. Daher gibt es keine genaueren Angaben zu den behandelten Objekten und Maßnahmen. Durch diese Quellen wird aber ersichtlich, dass gerade die Werkstättenleiterinnen in den Ateliers für Email- und Textilarbeiten (Adele von Stark und Rosalia Rothansl) zur Jahrhundertwende Pioniere der Objektrestaurierung waren. Die erste offizielle Restaurierungsklasse, das "Atelier für Kunstweberei und Restaurierung", bestand von 1902-1910. Informationen und Einblicke in die erstaunlich zeitgemäße Methodik und Ethik der Konservierungswissenschaft gegen Ende des 19. Jahrhunderts geben zwei Wiener Kongresse (Erster Kunstwissenschaftlicher Kongress, 1873 und Enquete zur Konservierung von Kunstgegenständen, 1904), an welchen Kuratoren des Kunstgewerbemuseums mitgewirkt haben.Eine neue Ära für die Konservierungswissenschaft und Restaurierung an der Universität für angewandte Kunst begann nach dem Zweiten Weltkrieg. Otto Nedbal, ein erfahrener Metallrestaurator, wurde an die Hochschule berufen und übernahm zunächst die bestehende Emailklasse. 1964 gründete er die erste Meisterklasse für die Restaurierung von Metall- und Emailarbeiten. Die Lehrinhalte und die Diplomanforderungen waren in den kommenden 40 Jahren kontinuierlicher Entwicklung ausgesetzt. 1980 wurde durch Nedbals Nachfolger Hubert Dietrich die Fachrichtung Gemälderestaurierung als zusätzlicher Studienschwerpunkt an der Angewandten eingeführt. Die Fachbereiche Stein- und Textilrestaurierung konnten unter der neuen Leitung von Gabriela Krist im Zuge der Umstrukturierung der Universität im Jahr 2000 weiters etabliert werden, so dass die Angewandte heute über vier Fachbereiche der Konservierung- und Restaurierung verfügt.